Khat chewing and cirrhosis in Somaliland: Case series - Hawa D. Mahamoud; Sabah Mohammed Muse; Lewis R. Roberts; Philip R. Fischer; Michael S. Torbenson; Tim Fader (AOSIS, 2016)
Background: Khat chewing is common especially among men in East Africa and Yemen. It is generally viewed by the populace as a benign social custom. Several studies of ethnic Somali immigrants to Western countries suggest an association between khat chewing and hepatotoxicity, but the risk of hepatotoxicity related to khat chewing within African settings is not documented. Aim: To identify and describe liver disease without evidence of alcohol exposure or infectious etiology in khat chewers. Settings: A university-affiliated teaching hospital in Somaliland. Methods: Cases of cirrhosis of unknown cause were identified from the clinical practice of Al Hayatt Hospital in Borama, Somaliland, during 14 months beginning December 2012. Results: Eight Somali men aged 27-70 years living in Somaliland were identified with cirrhosis of otherwise unknown cause. All chewed khat habitually for many years (15-128 bundles per day times years of use). A liver biopsy of one man was consistent with khat hepatotoxicity. Four of the eight men died during the study period.Conclusion: Khat chewing may be associated with health consequences including severe hepatotoxicity with cirrhosis.